KEBUTUHAN INFORMASI PETANI PADA LAHAN SAWAH MARJINAL (Kasus Desa Wadas Kecamatan Kandangan Kabupaten Temanggung) - Ihsaniyati, Hanifah; Kusnandar, Kusnandar; Padmaningrum, Dwiningtyas (Universitas Sebelas Maret, 2012)
Information is very important to reach purpose included for a farmer. The farmers tilling the farm which can only depend on rain water need information to survive, solve problems, lessen uncertainty, increase welfare, and to compete with other competitors. In accordance with the new paradigm in development and communication, the information presented by agricultural information organization should come from the need of information which is really felt by farmers. Being known from the previous study, the fact in the location of research indicates that agricultural extensions program was not really arranged with the farmers themselves or based on the need of information of farmer. Therefore, the purpose of this research is to fins the farmers’ need of information. The method of research which is used qualitative approach and constructive paradigm. The result of research indicates that the information need by farmers are concerning cultivation, capitalization, marketing, the rule of government and agricultural extension.